Associations between serum 25– hydroxyvitamin D concentrations and assisted reproductive technology outcomes in women with polycystic ovary syndrome: a cohort study - Guo, Li; Zheng, Xianhua; Gu, Chunming; Zhang, Zhili; Zhang, Xiaodan; Ruan, Xiaolin; Li, Hongyu; Mai, Qiongdan; Wu, Weixiang; Luo, Mingyong (Frontiers in Endocrinology, 2025)
BackgroundThe impact of serum vitamin D levels on the success of assisted reproductive technology (ART) among women with polycystic ovary syndrome (PCOS) has not been fully explored.MethodsThis cohort study enrolled 111 patients with PCOS who underwent in vitro fertilization (IVF) or intracyto–plasmic sperm injection (ICSI) treatment at Guangdong Women and Children Hospital from January 2022 to October 2024. Serum 25–hydroxyvitamin D [25(OH)D] concentrations were measured before embryo transfer (ET). The outcomes included the pregnancy rate, live birth rate, and early miscarriage rate. Multivariable logistic regression and the receiver operating characteristic (ROC) curve analyses were performed to evaluate predictive thresholds.ResultsPatients achieving clinical pregnancy (n=76, 68.47%) exhibited significantly higher pre–ET 25(OH)D levels (65.28 ± 18.90 vs. 52.22 ± 15.14, nmol/L, P < 0.001) and luteinizing hormone (LH) levels (9.52 ± 6.37 vs. 6.94 ± 4.52, IU/L, P = 0.021) compared to non–pregnant counterparts. Logistic regression, after adjusting for LH, demographics and hormonal profiles, revealed that 25(OH)D was significantly associated with pregnancy (B = 0.13, P = 0.030). ROC analysis identified 67.95 nmol/L as the optimal 25(OH)D cutoff for predicting pregnancy (with an area under the curve of 0.703, a specificity of 94.3%, and a sensitivity of 36.8%). Furthermore, pregnancies with pre–ET 25(OH)D ≥67.95 nmol/L had significantly higher live birth rates (75.00% vs. 52.08%, P = 0.049). Live birth cases maintained higher 25(OH)D levels than early miscarriages (67.63 ± 19.32 vs. 58.22 ± 16.01, nmol/L, P = 0.042).ConclusionsPre–ET serum vitamin D levels may serve as a modifiable biomarker for optimizing ART success in women with PCOS, associated with enhanced pregnancy likelihood and live birth outcomes. Systematic vitamin D supplementation prior to ET warrants further investigation as a potential adjuvant strategy.Clinical Trial Registrationhttps://www.medicalresearch.org.cn, identifier MR-44-25-016940.